English Language Education for Graduate Employability in Vietnam - Nghia, Tran Le Huu.; Tran, Ly Thi.; Ngo, Mai Tuyet; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2024)
This open access book examines the teaching and learning of English for employability in Vietnamese higher education. Its content is framed within one country to better examine the research issues within the influence of contextual factors. This book investigates how English can contribute to the development of students' employability capitals, particularly in the aspects of human capital, social capital, cultural capital, identity capital, and psychological capital. It presents employers' and employees$1 (Bperspectives of how and why English is increasingly important for career development. This book is a collection of discussions and viewpoints from teachers, students, and other stakeholders like employers, graduates, and course coordinators on current practices and their proposed improvements to prepare students for their future education, work and life. Based on empirical evidence, this book calls for repositioning English language education within the employability agenda to elevate its status and increase stakeholders' engagement. This book contributes to current debates on advancing the effectiveness of English language education in non-English speaking countries, as a response to internationalization and globalization.s
The Emergence of English Language Education in Non-English Speaking Asian Countries -- Current English Education in Vietnam: Policy, Practices and Challenges -- English Language Skills and Employability: A Theoretical Framework -- English Education and University Students$1 (BDevelopment of Human Capital -- English Language Education and Students$1 (BDevelopment of Social Capital -- The Development of Cultural Capital Through English Education and its Contributions to Graduate Employability -- The Contribution of English Language Education to Students$1 (BDevelopment of Soft Skills and Personal Attributes -- The Role of English Language Learning Experiences in the Development of TESOL Preservice Teachers$1 (BIdentity Capital -- Graduates$1 (BFeedback on the Contribution of General English Courses to their English Skills for Work Purposes -- Perspectives of English Teachers on the Effectiveness of the General English Program on Students$1 (BEmployability: A Case Studyin Vietnam -- English for Specific Purposes Courses and Vietnamese Graduates$1 (BEmployability -- English-medium-instruction in Vietnamese Universities: Pitfalls, Accomplishments, and Impact on Graduate Employability -- Vietnamese EFL Learners$1 (BPerspectives on Learning English Online and Employability -- Vietnamese Teachers of English Perceptions and Practices of Culture in Language Teaching -- Repositioning and Modifying the Contemporary Approach to English Language Education for Vietnamese Graduate Employability Enhancement. .s
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Language and languages -- Study and teaching; Education, Higher; Education and state; Educational sociology; Language Education; Higher Education; Educational Policy and Politics; Sociology of Education